SOLVING TRAFFIC CONGESTION FROM THE DEMAND SIDE - Ge, Ying-En; Prentkovskis, Olegas; Tang, Chunyan; Saleh, Wafaa; Bell, Michael G. H.; Junevičius, Raimundas (Promet - Traffic&Transportation, 2015)
It is nowadays widely accepted that solving traffic congestion from the demand side is more important and more feasible than offering more capacity or facilities for transportation. Following a brief overview of evolution of the concept of Travel Demand Management (TDM), there is a discussion on the TDM foundations that include demand-side strategies, traveler choice and application settings and the new dimensions that ATDM (Active forms of Transportation and Demand Management) bring to TDM, i.e. active management and integrative management. Subsequently, the authors provide a short review of the state-of-the-art TDM focusing on relevant literature published since 2000. Next, we highlight five TDM topics that are currently hot: traffic congestion pricing, public transit and bicycles, travel behavior, travel plans and methodology. The paper closes with some concluding remarks.